Primary Care-Led Health System in Indonesia - Nugraha, Ryan Rachmad; Claramita, Mora; Josef, Hari Kusnanto (Faculty of Medicine, Public Health, and Nursing, 2023)
It is a general consensus that investing more in primary care will lead to better health outcomes overall, and therefore, primary care should be the focus of development for health services. A body of evidence that intervention in primary care is cost-effective and reduces health system burden and disparities (1–7). Making primary care the focus of health development is crucial for the sustainability of the health system, particularly amidst the changing demographic landscape and disease burden. Designing health service or needs to start at primary care at its heart. This is concurrent with WHO 2008 report on Primary Care (8): “… focus of reform that reorganizes health services as primary care, i.e., around people’s needs and expectations so as to make them more socially relevant and more responsive to chancing world while produced better outcomes – service delivery reforms.”